Giant cell rich osteosarcoma of maxilla vs. giant cell granuloma: a diagnostic dilemma - Satpute, Satish S.; B., Nidhin S.; Nagarkar, Nitin M.; Gupta, Ashish; Arora, Ripudaman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Giant cell-rich osteosarcoma is a rare histological variant of osteosarcoma, accounting for 3% of all primary osteosarcomas and rarely occurring in the head and neck region. GCRO poses a significant diagnostic challenge radiologically and histopathologically, as it often presents with a benign appearance despite being a clinically aggressive osteosarcoma with a high tendency for recurrence. Meticulous surgical planning, a radical surgical approach, and postoperative radiotherapy are essential to prevent recurrence. We are discussing the case of a 21-year-old male patient diagnosed with Giant Cell-Rich Osteosarcoma of the maxilla. This case highlights the diagnostic dilemma associated with GCRO, the surgical approach employed, and the subsequent reconstruction process.